Sine qua non larva, turmoil and disdain: Responsiveness to ‘Covid-19 face-mask’ at Ogunpa, Ibadan, Nigeria - Abiodun Akande; John Adenle (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This research is a criticism addressing the formal and ergonomic analysis of Covid-19 face-masks at Giwa Adini, Ogunpa market, Ibadan, Nigeria. However, the research doubles as an ‘interrogative’ tool to elicit narratives on the responsiveness of illiterate and semi-literate traders at Giwa Adini on the advent of the coronavirus. Employing the survey technique, 100 randomly selected respondents were interviewed. The result obtained identifies five fabric mask types in the study area, the cup-shaped fabric mask being the most popular because of its adaptability to extant aso ebi culture. Other extemporized masks, reminiscent of traditional egungun masks, were also observed. With regards to the response to Covid-19, 21 respondents consider the coronavirus as falsehood, 23 claim it is God’s affliction, 43 agree to its reality, but query its low epidemiology and only 13 appear informed. The research showcases a variety of perceptions of Nigerians towards Covid-19,confirming the gross ignorance about the disease and their nonchalant attitude towards it.